A Hybrid Context -Knowledge Representation Model for Arabic Next Word Prediction - Noralhuda N. Alabid (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2026)
One of the controversial topics that has been raised in recent decades. Several approaches involving deep learning and machine learning was implemented to investing in the field of next word prediction in multiple language. In Arabic contexts, this topic is still challenges and in its early stages which need more investigation researches. this field suffers from lakes of robust model that designed specifically for predicted next Arabic word and high-quality dataset that used to develop this domain. This paper proposed a parallel hybrid model (AraBERT- knowledge graph) that augmented the pre-trained AraBERT model with knowledge graph to significantly enhanced next word prediction in Arabic corpus. The constructed of the proposed model involved integrating the AraBERT’s contextual vectors with entities of embedding of knowledge graph (KG). The SANAD dataset (195k articles) was used train this model. The model achieved an accuracy of 90% and an F1-score of 91% which outperformed several of fine adaption baseline models including AraGPT-2 (84.8) and AraBERT (82.6%). The significant improvement in results indicates that the combining of contextual and knowledge based has a promising direction for advancing several of Arabic language application including Arabic text prediction, understanding, and auto-generation, and other NLP application.